Nomina Sacra in Codex E - Tuckett, Christopher M. (The journal of theological studies, 2006)
Codex E is a bi-lingual manuscript containing the text of Acts in Greek and Latin. The use of so-called ‘nomina sacra’ in the manuscript presents one or two unusual features. In the Greek column, most of the expected abbreviations occur; but there are over twenty occurrences where one would expect to find an abbreviation for one of the four alleged ‘base’ words of the system (God, Christ, Jesus, Lord) but where the word is written in full. Proportionally (in relation to the length of the manuscript), this figure may be unusually high. In the Latin column, there are virtually no abbreviations at all, a phenomenon which is very unusual amongst Latin biblical manuscripts. The article attempts primarily to present this evidence. In addition, some possible further considerations are offered which might suggest (albeit tentatively) that the number of non-abbreviations in the Greek column may have been even higher in an earlier Vorlage of the text. Hence codex E appears to be a witness to the fact that the abbreviations of some of the key words, even in Christian biblical manuscripts, may not have been as uniform as some in recent studies have maintained.